Tantangan Terapi Hipernatremia Refrakter pada Pasien dengan Pneumonia Komunitas dan Gagal Ginjal Akut: Sebuah Laporan Kasus. - Ni Putu Yusica Maylasari; Ketut Suryana (Jurnal Kesehatan Holistic, 2026)
Hypernatremia is a serious electrolyte disorder associated with high mortality, particularly in patients with renal impairment and decreased fluid intake. We report the case of a 70-year-old woman presenting with decreased consciousness, slow speech, and difficulty communicating. Laboratory evaluation revealed a serum sodium level of 163 mmol/L, elevated urea and creatinine levels, and bilateral infiltrates on chest radiography suggestive of community-acquired pneumonia. The diagnosis of severe hypernatremia with Community-Acquired Pneumonia and Acute Kidney Injury was established. Initial therapy consisted of intravenous 0.9% sodium chloride followed by Dextrose 5% (D5W), with a correction target not exceeding 10–12 mmol/L per 24 hours, along with intravenous furosemide to promote natriuresis. Close monitoring of electrolytes, urine output, and renal function was maintained throughout hospitalization. After five days, serum sodium gradually decreased to 142 mmol/L, and the patient’s level of consciousness improved without neurological complications. This case highlights the therapeutic challenges of refractory hypernatremia in patients with pulmonary infection and renal dysfunction and underscores the importance of gradual fluid correction and multidisciplinary collaboration to achieve optimal clinical outcomes.